Gut microbiome and stages of diabetes in middle-aged adults: CARDIA microbiome study - Hu, Yi-Han; Meyer, Katie; Lulla, Anju; Lewis, Cora E.; Carnethon, Mercedes R.; Schreiner, Pamela J.; Sidney, Stephen; Shikany, James M.; Meirelles, Osorio; Launer, Lenore J. (Nutrition & metabolism, 2023)
Background Animal and human studies suggest the gut microbiome is linked to diabetes but additional data are needed on the associations of the gut microbiome to specific diabetes characteristics. The aim of this study was to examine the associations of gut microbiome composition to insulin resistance [Homeostatic Model Assessment of Insulin Resistance (HOMA-IR)], duration of diabetes, and 4 stages of diabetes [normoglycemia, pre-diabetes, and diabetes with (+) and without (−) medication for diabetes]. Methods Data are from a sub-sample (n = 605) of Black and White participants from the 30-year follow-up exam of the prospectively followed community-based Coronary Artery Risk Development in Young Adults cohort (2015–2016; aged 48–60 years). Stool samples were collected and sequenced using the 16S ribosomal RNA method. Microbial measures included: α diversity (within-person), β diversity (between-person), and taxonomies. All analyses were adjusted for demographic, clinical, lifestyle factors, and use of relevant medications (full adjustment). Multivariate linear regression models were used to assess the association of diabetes characteristics with α diversity and genera abundance, while the association with β diversity was analyzed using permutational multivariate analysis of variance. Statistical significance was set to p -value < 0.05 for α and β diversity analyses and to q-value < 0.1 for genera abundance analyses. Results There were 16.7% of participants with pre-diabetes, and 14.4% with diabetes (9% diabetes+) with median (interquartile range) diabetes duration of 5 (5–10) years. In the fully adjusted models, compared to those with no diabetes, longer diabetes duration and the diabetes + group had a lower α diversity. There were significant differences in β diversity across diabetes-related characteristics. A significantly reduced abundance of butyrate-producing genera was associated with higher HOMA-IR (ex., Anaerostipes and Lachnospiraceae_UCG.004 ), longer diabetes duration (ex., Agathobacter and Ruminococcus ), and diabetes + (ex., Faecalibacterium and Romboutsia ). Conclusions Our results suggest that an adverse alteration of gut microbiome composition is related to higher insulin resistance, longer diabetes duration, and is present in those persons with diabetes using medications. These diabetes-related characteristics were also associated with lower levels of certain butyrate-producing bacteria that produce health-promoting short‐chain fatty acids. Understanding the role of gut microbiota in glucose regulation may provide new strategies to reduce the burden of diabetes.